Preparation method of sphere-like nano boehmite and sphere-like nano aluminum oxide
Through the combination of pickling pretreatment and low-temperature hydrothermal reaction combined with calcination method, the cost and crystallinity problems in the preparation of spherical nanoboehmite and alumina are solved, and high-efficiency and low-energy consumption nanomaterial preparation is achieved, which is suitable for catalysts, adsorbents, battery separators, ceramic materials and electronic devices.
Patent Information
- Application Number
- CN202510713185.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-30
- Publication Date
- 2025-09-05
AI Technical Summary
The prior art is difficult to prepare spherical nanoboehmite and spherical nanoalumina with complete crystallinity at low cost and short process, and the traditional methods have problems such as high cost, imperfect crystallization morphology, and uneven particle size distribution.
The industrial alumina powder was pretreated by pickling, and the ρ-alumina hydration reaction was used to generate boehmite seeds, combined with pH regulator and crystal growth guide agent, and carried out a low-temperature hydrothermal reaction, and then calcined to prepare spherical nanoboehmite and alumina.
It has achieved low-cost and short-process preparation of spherical nanoboehmite and alumina with complete crystallinity, reducing energy consumption, avoiding dangerous operations of high temperature and high pressure, and the purity and consistency of products meet international standards and are suitable for large-scale production.
Smart Images

Figure CN120589767A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of fine alumina, and in particular to a preparation method of spherical nano-boehmite and spherical nano-alumina. Background Art
[0002] Boehmite (γ-AlOOH) is a hydrated aluminum oxide with a layered structure, interconnected by hydrogen bonds between hydroxyl groups. Each layer is composed of AlO₆ octahedra, each consisting of parallel double chains of AlO₆ octahedra centered around an aluminum atom. Each aluminum atom is surrounded by six oxygen atoms, with hydroxyl groups stacked between the layers to form an AlOOH layer. The surface oxygen exists as hydroxyl oxygens, linked by hydrogen bonds to form an ordered layered structure. Due to boehmite's crystal structure and surface hydration / hydroxylation, high-surface-area aluminum oxide prepared using boehmite as a precursor exhibits excellent properties and acid-base resistance, playing an indispensable role in numerous chemical processes, including adsorption and catalysis. Boehmite's rich hydroxyl group content, high porosity, high interfacial free energy, excellent dispersibility, high heat resistance, and low hardness have led to its widespread application in adsorbents, flame retardants, battery separators, coatings, and optically transparent materials, attracting increasing attention from both industry and research. Quasi-spherical nano-boehmite and quasi-spherical nano-alumina powders have small size surface effects, quantum size effects, volume effects, etc. Their special morphology and size can produce unique electrical, optical, magnetic, thermal, mechanical and chemical properties, and have a wide range of applications.
[0003] The main methods for synthesizing boehmite powder include the following: sol-gel method, electrochemical method, hydrothermal method, anion competition method, evaporation method, seed induction method, etc. Among them, the hydrothermal method has attracted much attention in recent years due to its designable morphology, environmental friendliness, and excellent product performance. However, it has disadvantages such as high cost, imperfect crystal morphology, uneven particle size distribution, and imperfect spherical growth. On the other hand, it is also a technical challenge to achieve both nanoparticle size and spherical morphology for spherical nano-alumina powder. At present, it mainly relies on raw material selection, sand milling and calcination, and the addition of mineralizers to achieve growth regulation. Mineralizers are corrosive to equipment and can easily cause uneven mixing, affecting the crystal morphology structure and particle size distribution. How to prepare a low-cost, short-process, spherical nano-boehmite with perfect crystallinity, and then use boehmite as a raw material to calcine to prepare nano-spherical alumina powder, and obtain spherical nano-boehmite and alumina powder is an important research direction in this field. Summary of the Invention
[0004] The present application provides a method for preparing spherical nano-boehmite and spherical nano-alumina, so as to provide a method for preparing spherical nano-boehmite with a short process and perfect crystallinity.
[0005] In a first aspect, an embodiment of the present application provides a method for preparing spherical nano-boehmite, the method comprising:
[0006] Performing acid washing pretreatment on industrial alumina powder to obtain a first pretreated raw material;
[0007] hydrating ρ-alumina with water to obtain a second pretreated slurry containing boehmite and bayerite; the hydration reaction is carried out by heating in a water bath;
[0008] mixing the first pretreated raw material, the second pretreated slurry, a pH regulator, and a crystal growth regulator to obtain a mixed slurry; and
[0009] The mixed slurry is subjected to a hydrothermal reaction to obtain spherical nano-boehmite powder;
[0010] Among them, the pH regulator includes one or more of organic acid, inorganic acid, organic base and inorganic base, and the crystal growth regulator includes one or more of surfactant, polymer and biomacromolecule; the reaction temperature of the hydrothermal reaction is 140℃~180℃, and the reaction time of the hydrothermal reaction is 2.5h~4h.
[0011] Optionally, the mass of the pH regulator is 0.1% to 0.5% of the mass of the solids in the mixed slurry; and / or,
[0012] The pH regulator includes one or more of dodecylbenzenesulfonic acid, stearic acid, lauric acid, oleic acid, citric acid, tartaric acid, ascorbic acid, acetic acid, oxalic acid and carbonic acid.
[0013] Optionally, the mass of the crystal growth directing agent is 0.05% to 0.2% of the mass of the solid in the mixed slurry; and / or,
[0014] The crystal growth directing agent includes one or more of lecithin, fatty acid monoglyceride, fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether, alkyl alcohol polyoxyethylene ether, dodecyltrimethylammonium chloride, polyquaternium-7, triethanolamine oleate, fatty acid monoglyceride, Span 60, Tween 65 and polyethylene glycol.
[0015] Optionally, the solid content of the mixed slurry is 160 g / L to 210 g / L.
[0016] Optionally, the industrial alumina powder is subjected to acid washing pretreatment to obtain a first pretreated raw material, comprising:
[0017] Industrial alumina powder, water and strong acid are mixed and stirred for a first time to perform pickling pretreatment to obtain a pickling slurry;
[0018] The pickling slurry is subjected to solid-liquid separation, and is rinsed with hot water during the solid-liquid separation process to obtain a first pretreated raw material.
[0019] Optionally, the mass ratio of the industrial alumina powder, the water and the strong acid is 100:(400-500):(3-5); and / or,
[0020] The first stirring speed is 260 rpm to 400 rpm, and the first stirring time is 1.5 h to 2.5 h; and / or,
[0021] The temperature of the hot water is 80°C to 100°C; and / or,
[0022] The moisture content of the first pretreated raw material is 4.2% to 8.5%.
[0023] Optionally, the hydration reaction of ρ-alumina with water to obtain a second pretreated slurry containing boehmite and bayerite comprises:
[0024] Stirring and heating ρ-alumina and water in a water bath to cause a hydration reaction between the ρ-alumina and the water to obtain a second pretreated slurry containing boehmite and bayerite; wherein the mass ratio of the ρ-alumina to water is 1:(2-3); and / or,
[0025] The temperature of the hydration reaction is 28° C. to 40° C., and the time of the hydration reaction is 20 min to 50 min.
[0026] In a second aspect, the present application provides a method for preparing spherical nano-alumina, the method comprising:
[0027] The spherical nano-boehmite prepared by the method described in any one of the embodiments of the first aspect is calcined to obtain spherical nano-alumina powder; the calcination temperature is 1150° C. to 1250° C., and the calcination time is 1.5 h to 2.5 h.
[0028] In a third aspect, the present application provides an application of spherical nano-boehmite prepared by the method described in any one of the embodiments of the first aspect, wherein the spherical nano-boehmite powder is used to prepare a catalyst, an adsorbent or a battery separator.
[0029] In a fourth aspect, the present application provides an application of spherical nano-alumina prepared by the method described in the embodiment of the second aspect, wherein the spherical nano-alumina powder is used to prepare ceramic materials, electronic devices or optical materials.
[0030] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:
[0031] The present invention provides a method for preparing spherical nano-boehmite, comprising: subjecting industrial alumina powder to an acid wash pretreatment to obtain a first pretreated raw material; subjecting rho-alumina to a hydration reaction with water to obtain a second pretreated slurry containing boehmite and bayerite; heating the hydration reaction in a water bath; mixing the first pretreated raw material, the second pretreated slurry, a pH regulator, and a crystal growth regulator to obtain a mixed slurry; and subjecting the mixed slurry to a hydrothermal reaction to obtain spherical nano-boehmite powder. By utilizing boehmite generated by low-temperature hydration of the raw material rho-alumina as a seed crystal, lowering the hydrothermal reaction temperature, and adding a pH regulator and a crystal growth director, the growth rate of each crystal face is synergistically promoted, the centripetal contraction force of liquid surface molecules is promoted, and the surface tension can minimize the surface area of the droplet, reducing the surface potential energy, and promoting the boehmite generated by the hydrothermal reaction to assume a spherical shape. This provides a method for preparing spherical nano-boehmite with a short process and perfect crystallinity. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0033] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without any creative work.
[0034] Figure 1 A schematic flow chart of a method for preparing spherical nano-boehmite provided in an embodiment of the present application;
[0035] Figure 2 A schematic flow chart of a method for preparing spherical nano-alumina provided in an embodiment of the present application;
[0036] Figure 3 This is a scanning electron microscope image of the spherical nano-boehmite powder provided in Example 2 of the present application;
[0037] Figure 4 This is the first scanning electron microscope image of the spherical nano-alumina powder provided in Example 2 of the present application;
[0038] Figure 5 A second scanning electron microscope image of the spherical nano-alumina powder provided in Example 2 of the present application;
[0039] Figure 6 This is the X-ray diffraction pattern of the spherical nano-alumina powder provided in Example 2 of the present application. DETAILED DESCRIPTION
[0040] To make the purpose, technical solutions, and advantages of the embodiments of this application more clear, the technical solutions in the embodiments of this application will be clearly and completely described below in conjunction with the drawings in the embodiments of this application. Obviously, the described embodiments are part of the embodiments of this application, not all of the embodiments. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of this application.
[0041] The range descriptions described in this article, such as numerical ranges, ratio ranges, etc., include all possible sub-ranges and single numerical values within the range. For example, the range description of "1 to 6" or "1~6" covers all sub-ranges from 1 to 6 (such as 1 to 3, 2 to 5, etc.) and single numbers (such as 1, 2, 3, 4, 5, 6). Unless otherwise specified, the terms "including", "comprising", etc. used in this article mean "including but not limited to"; relational terms such as "first" and "second" are only used to distinguish different entities or operations, and do not imply an actual sequence or association relationship; "and / or" means that multiple situations can exist alone or at the same time; expressions such as "at least one", "multiple", and "at least one" refer to any combination of corresponding objects, including a combination of single or multiple objects. The proportional relationships involved in the article, such as mass ratios, molar ratios, etc., should be understood as the corresponding relationship between the first and second terms of the proportional formula in the order of description. The raw materials, reagents, instruments and equipment used in this article can be purchased on the market or prepared by existing methods.
[0042] Figure 1 A schematic flow chart of a method for preparing spherical nano-boehmite provided in an embodiment of the present application.
[0043] like Figure 1 As shown, the present application provides a method for preparing spherical nano-boehmite, the method comprising:
[0044] S1. Pre-treating industrial alumina powder by pickling to obtain a first pre-treated raw material;
[0045] Acid washing pretreatment can remove impurities (Fe, Si, Na, etc.) in industrial alumina, expose the active surface, and improve the uniformity of subsequent reactions and product purity.
[0046] In some embodiments, the step of subjecting the industrial alumina powder to acid washing pretreatment to obtain a first pretreated raw material comprises:
[0047] Industrial alumina powder, water and strong acid are mixed and stirred for a first time to perform pickling pretreatment to obtain a pickling slurry;
[0048] The pickling slurry is subjected to solid-liquid separation, and is rinsed with hot water during the solid-liquid separation process to obtain a first pretreated raw material.
[0049] In some embodiments, the mass ratio of the industrial alumina powder, the water, and the strong acid is 100:(400-500):(3-5); and / or,
[0050] The first stirring speed is 260 rpm to 400 rpm, and the first stirring time is 1.5 h to 2.5 h; and / or,
[0051] The temperature of the hot water is 80°C to 100°C; and / or,
[0052] The moisture content of the first pretreated raw material is 4.2% to 8.5%.
[0053] In some embodiments, the mass ratio of the industrial alumina powder to the hot water is 1:(4-5).
[0054] The acid used for pickling can be one or more of hydrochloric acid, sulfuric acid, and nitric acid, which can dissolve metal oxide impurities. The mass ratio of industrial alumina powder, water, and strong acid is limited to 100:(400-500):(3-5), which optimizes the solid-liquid contact area and ensures sufficient pickling without excessive corrosion of the alumina matrix. The stirring speed is limited to 260-400 rpm and the stirring time is limited to 1.5-2.5 hours. Mechanical shear force accelerates the detachment of impurities and avoids excessive dissolution of alumina due to localized high acid concentrations. The hot water temperature for hot water elution is limited to 80-100°C to remove residual acid and soluble salts, preventing impurities from interfering with boehmite crystallization in subsequent reactions. The moisture content of the first pretreated raw material is controlled to 4.2%-8.5%, that is, the moisture content of the filter cake after solid-liquid separation is controlled to 4.2%-8.5%, thereby controlling the filter cake's fluidity and facilitating the subsequent preparation of a mixed slurry. For example, the mass ratio of industrial alumina powder, water and strong acid can be 100:400:3, 100:400:3.5, 100:400:4, 100:400:4.5, 100:400:5, 100:500:3, 100:500:3.5, 100:500:4, 100:500:4.5, 100:500:5, etc. The speed of the first stirring can be 260 rpm, 280 rpm, ... m, 300rpm, 340rpm, 380rpm, 400rpm, etc., the first stirring time can be 1.5h, 1.7h, 1.9h, 2.1h, 2.3h, 2.5h, etc.; the temperature of the spraying hot water can be 80℃, 85℃, 90℃, 95℃, 100℃, etc.; the moisture content of the first pretreated raw material can be 4.2%, 4.5%, 5.0%, 5.5%, 6.5%, 7.5%, 8.5%, etc.
[0055] S2, hydrating the ρ-alumina with water to obtain a second pretreated slurry containing boehmite and bayerite; the hydration reaction is carried out by heating in a water bath;
[0056] The hydration reaction of p-alumina produces a mixed slurry of boehmite (AlOOH) and bayerite (Al(OH)3). The boehmite serves as a seed crystal to induce directional crystallization in the subsequent hydrothermal reaction. Specifically, the hydration reaction equation is as follows: p-Al2O3 + 2H2O → AlOOH (boehmite) + Al(OH)3 (bayerite).
[0057] In some embodiments, the hydration reaction of rho-alumina with water to obtain a second pretreated slurry containing boehmite and bayerite comprises:
[0058] Stirring and heating rho-alumina and water in a water bath to cause a hydration reaction between the rho-alumina and the water to obtain a second pretreated slurry containing boehmite and bayerite;
[0059] wherein the mass ratio of the ρ-alumina to water is 1:(2-3); and / or,
[0060] The temperature of the hydration reaction is 28° C. to 40° C., and the time of the hydration reaction is 20 min to 50 min.
[0061] The temperature of the hydration reaction is limited to 28°C to 40°C, and ρ-Al2O3 reacts with water to form boehmite and bayerite. The hydration reaction time is within 50 minutes, and boehmite is dominant, acting as a seed to induce the subsequent hydrothermal reaction. In a short time (<20 minutes), the boehmite seeds are insufficient, and in a long time (>50 minutes), the proportion of bayerite is too high, which weakens the seed induction effect. Boehmite acts as a seed to reduce the subsequent hydrothermal temperature, and bayerite provides nucleation sites to synergistically promote crystallization. Exemplarily, the temperature of the hydration reaction can be 28°C, 30°C, 32°C, 34°C, 36°C, 38°C, 40°C, etc., and the time of the hydration reaction can be 20 minutes, 25 minutes, 30 minutes, 35 minutes, 40 minutes, 45 minutes, 50 minutes, etc.
[0062] S3, mixing the first pretreated raw material, the second pretreated slurry, a pH regulator and a crystal growth regulator to obtain a mixed slurry;
[0063] In some embodiments, the solid content of the mixed slurry is 160 g / L to 210 g / L.
[0064] The solid content of the mixed slurry is limited to 160g / L to 210g / L. The slurry has a low viscosity, which is conducive to the dispersion between particles, can reduce agglomeration, and can produce boehmite with a smaller particle size. However, if the solid content is less than 160g / L, the yield is low and the economic benefits are poor. If the solid content is higher than 210g / L, the slurry viscosity is high, the dispersion between particles is difficult, and agglomeration is easy. During the hydrothermal reaction, the boehmite precursor is difficult to convert into boehmite with a smaller particle size, and the average boehmite particle size is coarse. For example, the solid content of the mixed slurry can be 160g / L, 170g / L, 180g / L, 190g / L, 200g / L, 210g / L, etc.
[0065] In some embodiments, the pH regulator includes one or more of an organic acid, an inorganic acid, an organic base, and an inorganic base, and the crystal growth regulator includes one or more of a surfactant, a polymer, and a biomacromolecule.
[0066] In some embodiments, the mass of the pH regulator is 0.1% to 0.5% of the mass of the solids in the mixed slurry; and / or,
[0067] The pH regulator includes one or more of dodecylbenzenesulfonic acid, stearic acid, lauric acid, oleic acid, citric acid, tartaric acid, ascorbic acid, acetic acid, oxalic acid and carbonic acid.
[0068] The pH regulator can effectively change the pH of the mixed liquid system, change the isoelectric point of the mixed system, and especially effectively regulate the morphology of boehmite. At the same time, the pH regulator can also act as a precipitant to promote the hydrothermal reaction. As a precipitant, boehmite is precipitated through the hydrothermal reaction, which promotes the chemical reaction, makes the reaction faster and more complete, and can also remove iron impurity elements to improve purity. The pH regulator can also change the surface properties of the hydrate, combine with the surface of the hydrate and the fragmented pore structure, play a role in pore expansion and adsorption, and play a better role. Exemplarily, the mass of the pH regulator can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, etc. of the solid mass in the mixed slurry.
[0069] In some embodiments, the mass of the crystal growth directing agent is 0.05% to 0.2% of the mass of the solid in the mixed slurry; and / or,
[0070] The crystal growth directing agent includes one or more of lecithin, fatty acid monoglyceride, fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether, alkyl alcohol polyoxyethylene ether, dodecyltrimethylammonium chloride, polyquaternium-7, triethanolamine oleate, fatty acid monoglyceride, Span 60, Tween 65 and polyethylene glycol.
[0071] After the crystal growth directing agent is dissolved in water, it can synergistically promote the growth rate of each crystal face, promote the centripetal contraction force of the liquid surface molecules, and the surface tension can shrink the surface area of the droplet to a minimum, reduce the surface potential energy, and promote the boehmite generated by the hydrothermal reaction to be spherical. At the same time, the pH regulator and the crystal growth directing agent can work together to reduce the surface energy by adsorbing on the crystal surface and induce isotropic growth. For example, the mass of the crystal growth directing agent can be 0.05%, 0.08%, 0.1%, 0.12%, 0.15%, 0.18%, 0.2%, etc. of the solid mass in the mixed slurry.
[0072] S4, subjecting the mixed slurry to a hydrothermal reaction to obtain spherical nano-boehmite powder;
[0073] During the preparation process of the present application, there is no need to add additional seed crystals. The boehmite generated by the low-temperature hydration of the raw material ρ-alumina is used as the seed crystal to reduce the hydrothermal reaction temperature. The addition of a pH regulator and a crystal growth directing agent can synergistically promote the growth rate of each crystal face and the centripetal contraction force of the liquid surface molecules. The surface tension can shrink the surface area of the droplet to a minimum, reduce the surface potential energy, and promote the boehmite generated by the hydrothermal reaction to be spherical.
[0074] In some embodiments, the reaction temperature of the hydrothermal reaction is 140° C. to 180° C., and the reaction time of the hydrothermal reaction is 2.5 h to 4 h.
[0075] The embodiment of the present application reduces the hydrothermal temperature (traditionally 150°C to 220°C) and shortens the reaction time (traditionally 8h to 24h) by using ρ-alumina self-generated crystal seeds, thereby significantly saving energy consumption. If the temperature is <140°C, the reaction is incomplete and the boehmite crystallinity is low; if the temperature is >160°C, α-Al2O3 impurity phase is easily generated; 2.5h to 4h is the equilibrium window for grain growth and morphology control. Exemplarily, the reaction temperature of the hydrothermal reaction can be 140°C, 150°C, 160°C, 170°C, 180°C, etc., and the reaction time of the hydrothermal reaction can be 2.5h, 3h, 3.2h, 3.5h, 3.8h, 4h, etc.
[0076] Therefore, the embodiment of the present application provides a method for preparing spherical nano-boehmite with simple process, low production cost (low hydrothermal temperature), short flow and perfect crystallinity.
[0077] Figure 2 A schematic flow chart of a method for preparing spherical nano-alumina provided in an embodiment of the present application.
[0078] Based on a general inventive concept, such as Figure 2 As shown, the present application provides a method for preparing spherical nano-alumina, the method comprising:
[0079] S5. calcining the spherical nano-boehmite prepared by the method described in any one of the above embodiments to obtain spherical nano-alumina powder; the calcination temperature is 1150° C. to 1250° C., and the calcination time is 1.5 h to 2.5 h.
[0080] The embodiment of the present application prepares nano-spherical alumina powder by calcination, which has no agglomeration and good dispersibility. Not only spherical nano-boehmite powder is obtained, but also nano-spherical alumina powder can be obtained, filling the high-end application field and application scope. Compared with the existing hydrothermal boehmite products, the morphology and particle size distribution are regulated by hydrothermal method, and no subsequent grinding and dispersion is required, the crystal morphology is not destroyed, the cost is saved, and there is no agglomeration. By directly calcining boehmite, the spherical nano-morphology of the precursor boehmite is inherited, with a smaller nanoparticle size and a spherical shape. There is no need for subsequent grinding and dispersion, and the crystal morphology is not destroyed. The preparation method of spherical nano-alumina is enriched and the application scenario of the product is increased. For example, the calcination temperature can be 1150℃, 1170℃, 1190℃, 1200℃, 1230℃, 1250℃, etc., and the calcination time can be 1.5h, 1.7h, 1.9h, 2.1h, 2.3h, 2.5h, etc.
[0081] In some embodiments, the phase structure of the spherical nano-boehmite is a pure boehmite phase, the phase structure of the spherical nano-alumina powder is an α-alumina phase, and the α-phase conversion rate of the spherical nano-alumina powder is ≥95%.
[0082] Based on a general inventive concept, the present application provides an application of spherical nano-boehmite prepared by the method described in any one of the above embodiments, wherein the spherical nano-boehmite powder is used to prepare catalysts, adsorbents or battery separators.
[0083] Based on a general inventive concept, the present application provides an application of spherical nano-alumina prepared by the method described in the above embodiment, wherein the spherical nano-alumina powder is used to prepare ceramic materials, electronic devices or optical materials.
[0084] In summary, the method for preparing quasi-spherical nanoboehmite and alumina provided in this application, through process innovation and parameter optimization, achieves green preparation of high-purity, low-energy, and morphology-controllable nanomaterials, breaking through traditional technical bottlenecks and possessing broad application prospects in new energy, electronic devices, and other fields. Specifically, it has the following significant advantages:
[0085] (1) Efficient impurity removal and raw material activation: Acid pretreatment selectively dissolves metal oxide impurities (Fe, Si, Na, etc.) through strong acid to improve the purity of the raw materials; at the same time, the acid concentration (mass ratio 100:3~5) and mechanical stirring (260~400rpm) are precisely controlled to optimize the solid-liquid contact area and avoid excessive corrosion of the alumina matrix; in addition, high-temperature elution (80~100℃) effectively removes residual acid and soluble salts, reduces interference with subsequent reactions, and the filter cake moisture content (4.2%~8.5%) ensures the fluidity of the slurry.
[0086] (2) Self-generated seed-induced directional crystallization: The boehmite / bayerite mixed seed is generated in situ by the ρ-Al2O3 hydration reaction (28-40℃, 20-50min), eliminating the need for external seed addition and simplifying the process. At the same time, boehmite acts as a seed to lower the subsequent hydrothermal temperature (140-180℃), and bayerite provides nucleation sites, synergistically promoting the crystallization of high-purity boehmite at low temperatures. In addition, compared with the traditional hydrothermal method (150-220℃, 8-24h), it reduces energy consumption and shortens reaction time.
[0087] (3) Precise control of morphology and particle size: pH regulator (0.1-0.5%) and crystal growth director (0.05-0.2%) work synergistically to regulate anisotropic growth by adsorbing crystal surfaces and inhibit agglomeration; at the same time, the solid content of the mixed slurry (160-210 g / L) optimizes dispersibility and achieves a nanoscale spherical structure; in addition, surface tension drives the droplet to shrink, forming a high sphericity, which improves the performance of the material in catalysis, coating and other fields.
[0088] (4) Calcination inheritance and high conversion rate: The boehmite precursor is directly converted into α-Al2O3 by calcination (1150-125℃, 1.5-2.5h), with good morphology inheritance and complete retention of the nano-spherical structure; at the same time, the α phase conversion rate is ≥95%, there is no hard agglomeration, and the dispersion is excellent, avoiding the morphology damage caused by traditional grinding; in addition, the product is suitable for high-end ceramics, polishing and composite materials, filling the gap in the preparation technology of highly dispersed nano-alumina.
[0089] (5) Compatibility with green economy and industrialization: high raw material utilization rate, pickling waste liquid can be recycled, reducing environmental protection costs; at the same time, the entire process does not require high temperature and high pressure dangerous operations, and the equipment requirements are low, which is suitable for large-scale continuous production; in addition, the purity and consistency of boehmite and alumina products meet international standards, and the cost is lower than that of imported products.
[0090] The present application will be further described below in conjunction with specific examples. It should be understood that these examples are intended to illustrate the present application only and are not intended to limit the scope of the present application. The experimental methods in the following examples where specific conditions are not specified are generally measured according to industry standards. If there are no corresponding industry standards, then the methods are carried out according to general international standards, conventional conditions, or the conditions recommended by the manufacturer.
[0091] Example 1
[0092] This embodiment provides a method for preparing spherical nano-boehmite powder and spherical nano-alumina powder, which may include the following steps:
[0093] S11. Put 500g of industrial alumina powder into a beaker and add it to 2200ml of deionized water for acid washing pretreatment.
[0094] Acid washing was performed using hydrochloric acid at a rate of 4% based on the mass of the alumina powder. The slurry in the beaker was stirred for pretreatment at a speed of 300 rpm for 2 hours. The acid-washed sample was filtered and rinsed with 2000 ml of hot water to obtain a filter cake. The temperature of the hot water was 82°C. The filter cake had a moisture content of 5.2%. This filter cake served as the first pretreatment raw material.
[0095] S21. Add 200 g of ρ-alumina into a beaker and 500 ml of deionized water, stir and heat in a water bath to perform a hydration reaction, and obtain a second pretreated slurry containing boehmite and bayerite.
[0096] The water bath temperature was set at 30°C, and the hydration reaction time was set at 35 min.
[0097] S31. Mix the first pretreated raw material and the second pretreated slurry and add them into a reactor as a reaction aluminum source. Add a pH regulator and a crystal growth directing agent into the mixed slurry in the reactor to obtain a mixed slurry.
[0098] The solid content of the mixed slurry is 175 g / L. The pH adjuster is dodecylbenzenesulfonic acid. The amount of the pH adjuster added is 0.2% of the solid content of the mixed slurry. The crystal growth directing agent is polyquaternium-7. The amount of the crystal growth directing agent added is 0.1% of the solid content of the third mixed slurry.
[0099] S41, subjecting the mixed slurry to a hydrothermal reaction, filtering the slurry after the hydrothermal reaction, washing the filter cake, and microwave drying to obtain spherical nano-boehmite powder.
[0100] The hydrothermal reaction temperature is 145°C, the reaction time is 3 hours, and the drying temperature is 80°C.
[0101] Based on the quasi-spherical nano-boehmite powder, this embodiment also provides a method for preparing quasi-spherical nano-alumina, which may include the following steps:
[0102] S51. calcining the spherical nano-boehmite at a high temperature to obtain alumina powder.
[0103] Wherein, the calcination temperature is 1200° C. and the calcination time is 2.0 h.
[0104] Example 2
[0105] This embodiment provides a method for preparing spherical nano-boehmite powder and spherical nano-alumina powder, which may include the following steps:
[0106] S11. Put 500g of industrial alumina powder into a beaker and add it to 2000ml of deionized water for acid washing pretreatment.
[0107] Acid washing was performed using sulfuric acid at a rate of 4% by mass of the alumina powder. The slurry in the beaker was stirred for pretreatment at a speed of 300 rpm for 2 hours. The acid-washed sample was filtered and rinsed with 2000 ml of hot water to obtain a filter cake. The temperature of the hot water was 86°C. The filter cake had a moisture content of 6.2%. This filter cake served as the first pretreatment raw material.
[0108] S21. Add 200 g of ρ-alumina into a beaker and 500 ml of deionized water, stir and heat in a water bath to perform a hydration reaction, and obtain a second pretreated slurry containing boehmite and bayerite.
[0109] The water bath temperature was set at 30°C, and the hydration reaction time was set at 35 min.
[0110] S31. Mix the first pretreated raw material and the second pretreated slurry and add them into a reactor as a reaction aluminum source. Add a pH regulator and a crystal growth directing agent into the mixed slurry in the reactor to obtain a mixed slurry.
[0111] The solid content of the mixed slurry is 175 g / L. The pH adjuster is stearic acid. The amount of the pH adjuster added is 0.3% of the solid content of the mixed slurry. The crystal growth directing agent is fatty alcohol polyoxyethylene ether. The amount of the crystal growth directing agent added is 0.1% of the solid content of the third mixed slurry.
[0112] S41, subjecting the mixed slurry to a hydrothermal reaction, filtering the slurry after the hydrothermal reaction, washing the filter cake, and microwave drying to obtain spherical nano-boehmite powder.
[0113] The hydrothermal reaction temperature is 140°C, the reaction time is 2.5 hours, and the drying temperature is 80°C.
[0114] Based on the quasi-spherical nano-boehmite powder, this embodiment also provides a method for preparing quasi-spherical nano-alumina, which may include the following steps:
[0115] S51. calcining the spherical nano-boehmite at a high temperature to obtain alumina powder.
[0116] Wherein, the calcination temperature is 1200° C. and the calcination time is 2.0 h.
[0117] Example 3
[0118] The difference between this embodiment and embodiment 2 is that:
[0119] The pH regulator is ascorbic acid, and the amount of the pH regulator added is 0.5% of the solid content in the mixed slurry; the rest are consistent with Example 2.
[0120] Example 4
[0121] The difference between this embodiment and embodiment 2 is that:
[0122] The crystal growth directing agent is alkylphenol polyoxyethylene ether, and the amount of the crystal growth directing agent added is 0.2% of the solid content in the mixed slurry; the rest are consistent with Example 2.
[0123] Example 5
[0124] The difference between this embodiment and embodiment 2 is that:
[0125] The reaction temperature of the hydrothermal reaction was 170° C., and the reaction time was 3 h; the rest were the same as in Example 2.
[0126] Comparative Example 1
[0127] The difference between this comparative example and Example 2 is that:
[0128] The hydrothermal slurry was not added with the second pretreated slurry as a seed; the rest were the same as in Example 2.
[0129] Comparative Example 2
[0130] The difference between this comparative example and Example 2 is that:
[0131] No crystal growth inducer was added during the hydrothermal reaction; the rest of the steps were the same as those in Example 2.
[0132] Comparative Example 3
[0133] The difference between this comparative example and Example 2 is that:
[0134] The hydrothermal reaction temperature is 130° C.; the rest of the steps are the same as those in Example 2.
[0135] Comparative Example 4
[0136] The difference between this comparative example and Example 2 is that:
[0137] The spherical nano-boehmite was calcined at a high temperature to obtain alumina powder. The calcination temperature was 1150° C. and the holding time was 2 hours. The rest of the steps were the same as those in Example 2.
[0138] The hydrothermal products and calcined products obtained in Examples 1 to 5 and Comparative Examples 1 to 4 were analyzed and tested. The test results are shown in Table 1.
[0139] Table 1 Properties of hydrothermal products and calcined products of Examples 1 to 5 and Comparative Examples 1 to 4
[0140]
[0141]
[0142] According to Table 1, it can be seen that according to Example 2 and Comparative Example 1, without adding seed crystals, it cannot be completely converted into boehmite crystals at a low temperature of 140°C, and the phase cannot be completely transformed. According to Example 2 and Comparative Example 2, it can be proved that the crystal growth directing agent has a huge influence on the morphology of the hydrothermal product, and can promote the formation of spherical nano-boehmite. If it is not added, spherical nano-boehmite cannot be generated. According to Example 2 and Comparative Example 3, it can be proved that the hydrothermal temperature has a huge influence on the morphology of the hydrothermal product, and the appropriate hydrothermal temperature can promote the formation of spherical nano-boehmite. According to Example 2 and Comparative Example 4, it can be proved that the calcination temperature has a great influence on the conversion rate of the calcined product. When the calcination temperature is low, the calcined product can still inherit the nano-spherical shape of boehmite, but the conversion rate of the a phase in the calcined product is only 82.4%, which is a mixture of the three phases of a, θ, and δ.
[0143] Figure 3 This is a scanning electron microscope image of the spherical nano-boehmite powder provided in Example 2 of the present application.
[0144] Depend on Figure 3 It can be seen that the powder prepared by Example 2 is nano-sized, with a size between 30nm and 60nm, and is spherical. The particles have good dispersion, no adhesion, and a clear interface. No subsequent airflow dispersion is required, which reduces the process and reduces costs.
[0145] Figure 4 This is the first scanning electron microscope image of the spherical nano-alumina powder provided in Example 2 of the present application; Figure 5This is the second scanning electron microscope image of the spherical nano-alumina powder provided in Example 2 of the present application.
[0146] Figure 4 and Figure 5 It is a spherical nano-alumina powder with different magnifications. Figure 4 and Figure 5 From the scanning electron microscope image, it can be seen that the alumina powder is nano-sized, less than 150nm in size, spherical in shape, with good particle dispersion, no adhesion, clear interface, and no need for subsequent airflow dispersion, which reduces the process and reduces costs.
[0147] Figure 6 This is the X-ray diffraction pattern of the spherical nano-alumina powder provided in Example 2 of the present application.
[0148] Depend on Figure 6 It can be seen that the prepared powder is pure phase boehmite with sharp peaks, which proves that the crystallinity is good, the crystals are well developed and the particle size is small.
[0149] In addition, one or more technical solutions in the embodiments of the present application have at least the following technical effects or advantages:
[0150] 1. The process is simple, with low production costs, a short process, and perfect crystallinity. No additional seed crystals are required. The boehmite generated by the low-temperature hydration of the raw material ρ-alumina is used as the seed crystal, which reduces the hydrothermal reaction temperature. The addition of a pH regulator and a crystal growth directing agent synergistically promotes the growth rate of each crystal face and the centripetal contraction of the liquid surface molecules. Surface tension minimizes the surface area of the droplet, reducing the surface potential energy and causing the boehmite generated by the hydrothermal reaction to assume a spherical shape.
[0151] 2. Nano-spherical alumina powder is prepared by calcination, which has no agglomeration and good dispersibility. Not only nano-spherical boehmite powder is obtained, but also nano-spherical alumina powder can be obtained, filling the high-end application field and application scope. Compared with existing hydrothermal boehmite products, the morphology and particle size distribution are regulated by hydrothermal method, and there is no need for subsequent grinding and dispersion, which does not destroy the crystal morphology, saves costs, and has no agglomeration. Boehmite is directly calcined, inheriting the spherical nano-morphology of the precursor boehmite, with a smaller nanoparticle size and a spherical shape. It does not require subsequent grinding and dispersion, and does not destroy the crystal morphology. It enriches the preparation methods of spherical nano-alumina and increases the application scenarios of the product.
[0152] 3. The high surface area and open pores of spherical nanoalumina improve the loading efficiency of active components (such as Pt and Pd), making it suitable for automobile exhaust purification and petroleum cracking. Furthermore, its nanoscale particle size and low agglomeration properties enable the preparation of highly dense and tough structural ceramics (such as cutting tools and wear-resistant coatings). Furthermore, boehmite's layered structure is suitable for the adsorption of gases (such as CO2) and heavy metal ions, improving purification efficiency.
[0153] The foregoing is merely a list of specific embodiments of the present application, intended to enable those skilled in the art to understand or implement the present application. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application is not limited to the embodiments shown herein, but is intended to conform to the broadest scope consistent with the principles and novel features of the present application.
Claims
1. A method for preparing spherical nano-boehmite, the method comprising: Performing acid washing pretreatment on industrial alumina powder to obtain a first pretreated raw material; hydrating ρ-alumina with water to obtain a second pretreated slurry containing boehmite and bayerite; the hydration reaction is carried out by heating in a water bath; mixing the first pretreated raw material, the second pretreated slurry, a pH regulator, and a crystal growth regulator to obtain a mixed slurry; and The mixed slurry is subjected to a hydrothermal reaction to obtain spherical nano-boehmite powder; Among them, the pH regulator includes one or more of organic acid, inorganic acid, organic base and inorganic base, and the crystal growth regulator includes one or more of surfactant, polymer and biomacromolecule; the reaction temperature of the hydrothermal reaction is 140℃~180℃, and the reaction time of the hydrothermal reaction is 2.5h~4h.
2. The method according to claim 1, characterized in that The mass of the pH regulator is 0.1% to 0.5% of the mass of the solids in the mixed slurry; and / or, The pH regulator includes one or more of dodecylbenzenesulfonic acid, stearic acid, lauric acid, oleic acid, citric acid, tartaric acid, ascorbic acid, acetic acid, oxalic acid and carbonic acid.
3. The method according to claim 1, characterized in that The mass of the crystal growth directing agent is 0.05% to 0.2% of the mass of the solid in the mixed slurry; and / or, The crystal growth directing agent includes one or more of lecithin, fatty acid monoglyceride, fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether, alkyl alcohol polyoxyethylene ether, dodecyltrimethylammonium chloride, polyquaternium-7, triethanolamine oleate, fatty acid monoglyceride, Span 60, Tween 65 and polyethylene glycol.
4. The method according to claim 1, wherein The solid content of the mixed slurry is 160 g / L to 210 g / L.
5. The method according to claim 1, characterized in that The industrial alumina powder is subjected to acid washing pretreatment to obtain a first pretreated raw material, comprising: Industrial alumina powder, water and strong acid are mixed and stirred for a first time to perform pickling pretreatment to obtain a pickling slurry; The pickling slurry is subjected to solid-liquid separation, and is rinsed with hot water during the solid-liquid separation process to obtain a first pretreated raw material.
6. The method according to claim 6, characterized in that The mass ratio of the industrial alumina powder, the water and the strong acid is 100:(400-500):(3-5); and / or, The first stirring speed is 260 rpm to 400 rpm, and the first stirring time is 1.5 h to 2.5 h; and / or, The temperature of the hot water is 80°C to 100°C; and / or, The moisture content of the first pretreated raw material is 4.2% to 8.5%.
7. The method according to claim 1, characterized in that The step of hydrating ρ-alumina with water to obtain a second pretreated slurry containing boehmite and bayerite comprises: Stirring and heating ρ-alumina and water in a water bath to cause a hydration reaction between the ρ-alumina and the water to obtain a second pretreated slurry containing boehmite and bayerite; wherein the mass ratio of the ρ-alumina to water is 1:(2-3); and / or, The temperature of the hydration reaction is 28° C. to 40° C., and the time of the hydration reaction is 20 min to 50 min.
8. A method for preparing spherical nano-alumina, comprising: The spherical nano-boehmite prepared by the method according to any one of claims 1 to 7 is calcined to obtain spherical nano-alumina powder; the calcination temperature is 1150° C. to 1250° C., and the calcination time is 1.5 h to 2.5 h.
9. Use of the spherical nano-boehmite prepared by the method according to any one of claims 1 to 7, wherein the spherical nano-boehmite powder is used for preparing catalysts, adsorbents or battery separators.
10. Use of the quasi-spherical nano-alumina prepared by the method according to claim 8, wherein the quasi-spherical nano-alumina powder is used to prepare ceramic materials, electronic devices or optical materials.
Citation Information
Cited By
Spheroidal nano alpha-alumina and method for preparing the same
CN122586094A